2021
DOI: 10.1590/0001-3765202120191048
|View full text |Cite
|
Sign up to set email alerts
|

Performance of broiler breeders supplemented with organic and inorganic minerals

Abstract: The present study aimed to evaluate the use of organic and inorganic minerals in Cobb500 broiler breeder diet and its effects on the performance. The birds were housed in an experimental house at Poultry Laboratory of the Federal University of Santa Maria with 20 fl oor pens of 4.61m2 each. The experiment was conducted between 51st and 65 th weeks of age of birds. The design was completely randomized with four treatments and fi ve pen replicates with 22 hens and 2 roosters each. The treatments evaluated were: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The results indicated no difference in the production performance in terms of HDEP and egg mass production, aligning with the findings of Xiao et al (2015) and Jiang et al (2021) . As expected, HDEP decreased as the hen aged; the observed decline of nearly 10% in HDEP over the 10-wk period in our study aligns with the egg production trends observed in a study by Pedro et al (2021) . In that study, there were no differences in HDEP based on TM source in BB fed InO or OR sources of TM but they noted an age dependent decrease in HDEP from 62.1% at 55 WOA to 52.2% at 65 WOA, for InO and OR sources, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The results indicated no difference in the production performance in terms of HDEP and egg mass production, aligning with the findings of Xiao et al (2015) and Jiang et al (2021) . As expected, HDEP decreased as the hen aged; the observed decline of nearly 10% in HDEP over the 10-wk period in our study aligns with the egg production trends observed in a study by Pedro et al (2021) . In that study, there were no differences in HDEP based on TM source in BB fed InO or OR sources of TM but they noted an age dependent decrease in HDEP from 62.1% at 55 WOA to 52.2% at 65 WOA, for InO and OR sources, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that the inorganic form of Se has low bioavailability, accelerates oxidation processes and can be toxic, especially at high concentrations. In contrast, organic-Se and nano-Se exhibit low toxicity, high adsorption capacity, high bioavailability and high catalytic efficiency in chickens, sheep and goats [ 46 , 47 , 48 ]. Selenium is an important trace element that upregulates a vital component of the antioxidant defiance mechanism by controlling the body’s glutathione pool and Se-dependent antioxidant enzymes such as superoxide dismutase and glutathione peroxidase [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%